PROSES BERPIKIR KRITIS DAN PENALARAN MATEMATIS SISWA DALAM MEMECAHKAN MASALAH MATEMATIKA BERDASARKAN GAYA BELAJAR (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Critical thinking and mathematical reasoning skills are important competencies in mathematics learning. Each student has a different level of critical thinking and mathematical reasoning skills, which influence their understanding and solving mathematical problems. These differences are influenced by various characteristics, one of which is learning style. This study aims to analyze students' critical thinking and mathematical reasoning skills in solving mathematical problems based on their learning styles. The research method used is descriptive qualitative with a purposive sampling technique, resulting in 12 eighth-grade students as research subjects, two students each representing a single learning style or a combination of two learning styles. Data collection was carried out through questionnaires, tests, interviews, observations, and documentation. The results of the study show that students with visual and visual-auditory learning styles are able to fulfill all indicators of critical thinking and mathematical reasoning skills. Participants with an auditory learning style mastered the basic clarification indicators and concluded in critical thinking skills, as well as presenting mathematical statements and drawing conclusions in mathematical reasoning. Kinesthetic participants performed less than optimally in the basic support indicators for critical thinking skills, but had mastered all the mathematical reasoning indicators. Auditory-kinesthetic participants mastered the basic clarification and conclusion indicators for critical thinking skills, while for mathematical reasoning skills, they mastered the indicators for presenting statements, compiling evidence or reasons, and drawing conclusions. Meanwhile, visual-kinesthetic participants only mastered the basic clarification indicators for critical thinking skills and presenting mathematical statements for mathematical reasoning skills.